Regulatory mechanisms tuning ethylen signaling in plants - E. V. Zemlyanskaya; N. A. Omelyanchuk; A. A. Ermakov; V. V. Mironova (Вавиловский журнал генетики и селекции)
Plant hormone ethylene regulates a wide range of physiological processes during plant development and coordinates different stress responses. Among others ethylene controls such practically significant characteristics of agricultural crops as fruit ripening rates and plant tolerance to stress conditions. That is why understanding molecular mechanisms underlying ethylene action is one of the basic questions in plant biology that is addressed in the context of both fundamental research and application in agriculture. Ethylene biosynthesis from methionine amino acid and the main points of its signaling pathway from membrane receptors to effector genes are studied in details and widely reviewed. Far less is known about genetic regulation of these two processes although it is the one that ensures accurate plant reaction to different endogenous and exogenous signals and causes the multiplicity of different physiological responses to ethylene. This review summarizes data about regulatory mechanisms of ethylene biosynthesis and signaling. It reports the key transcriptional and post-translational regulatory factors which control expression and stability of the main components of ethylene biosynthesis and signaling pathways, and describes multiple feed-backs supplementing the linear model of ethylene signaling. Particular attention is given to the role of hormonal crosstalk in the process. Different mechanisms of hormonal interaction are illustrated by synergy or antagonism of ethylene and auxin, jasmonates, cytokinins, brassinosteroids. Possible molecular basics of multiplicity of different physiological responses to ethylene is also discussed.